Worksheet 6

Throughout this page, I will be using Laplace expansion repeatedly to calculate determinants of matrices. If you don't remember/know what that is, here are some resources:

Problem 1

  1. Denote by TijT_{ij} the elementary matrix obtained by exchanging the ii-th row and jj-th rows. Write TijT_{ij} in matrix form. Compute det(Tij)\det\p{T_{ij}}. Prove that det(Tijt)=det(Tij)\det\p{T_{ij}^t} = \det\p{T_{ij}}. Prove that Tij1=TijT_{ij}^{-1} = T_{ij}.

  2. Denote by Di(m)D_i\p{m} the elementary matrix obtained by multiplying the ii-th row by a scalar mm. Write Di(m)D_i\p{m} in matrix for. Compute det(Di(m))\det\p{D_i\p{m}}. Prove that det(Di(m)t)=det(Di(m))\det\p{D_i\p{m}^t} = \det\p{D_i\p{m}}. Prove that Di(m)D_i\p{m} is invertible if m0m \neq 0 with Di(m)1=Di(m1)D_i\p{m}^{-1} = D_i\p{m^{-1}}.

  3. We denote by Lij(m)L_{ij}\p{m} the elementary matrix obtained by adding to the ii-th row the jj-th row multiplied by a scalar mm. Write Lij(m)L_{ij}\p{m} in matrix form. Compute det(Lij(m))\det\p{L_{ij}\p{m}}. Prove that det(Lij(m)t)=det(Lij(m))\det\p{L_{ij}\p{m}^t} = \det\p{L_{ij}\p{m}}. Prove that Lij(m)1=Lij(m)L_{ij}\p{m}^{-1} = L_{ij}\p{-m}.

Solution.
  1. To compute TijT_{ij}, we can just figure out what it does to the standard basis {e1,,en}\set{e_1, \ldots, e_n} of Fn\F^n. If k{i,j}k \notin \set{i, j}, then the ii-th and jj-th rows of eke_k (or in other words, the ii-th and jj-th entries of eke_k) are both 00, so swapping those rows does nothing. I.e., Tijek=ekT_{ij} e_k = e_k. However, if k=ik = i, then we swap a 11 in the ii-th entry with a 00 in the jj-th entry, so Tijei=ejT_{ij} e_i = e_j. Similarly, Tijej=eiT_{ij} e_j = e_i. Thus, TijT_{ij} looks like

    Tij=(Tije1TijeiTijejTijen)=(101101).\begin{aligned} T_{ij} &= \begin{pmatrix} T_{ij}e_1 & \cdots & T_{ij}e_i & \cdots & T_{ij}e_j & \cdots & T_{ij}e_n \end{pmatrix} \\ &= \begin{pmatrix} 1 \\ & \ddots \\ & & 0 & \cdots & 1 \\ & & \vdots & \ddots & \vdots \\ & & 1 & \cdots & 0 \\ & & & & & \ddots \\ & & & & & & 1 \end{pmatrix}. \end{aligned}

    Most entries are 00 except on the diagonal and the 11's the were moved off the diagonal. The off-diagonal 11's have indices (i,j)\p{i, j} and (j,i)\p{j, i}.

    To compute the determinant, we perform Laplace expansion on the ii-th column first. Assuming i<ji < j, this expansion gives

    det(Tij)=(1)j+idet(11101).\det\p{T_{ij}} = \p{-1}^{j+i} \det \begin{pmatrix} 1 \\ & \ddots \\ & & 1 & \cdots & 1 \\ & & & \ddots & \vdots \\ & & & & 0 \\ & & & & & \ddots \\ & & & & & & 1 \end{pmatrix}.

    The matrix in the determinant is the minor we get from removing the jj-th row and ii-th column. Since the jj-th row is below the top-right 11, its row index doesn't change. However, because the ii-column is to the left, we shifted it to the left by 11. Thus, the 11 has index (i,j1)\p{i, j-1}. Laplace expanding in the (j1)\p{j-1}-th column gives

    det(Tij)=(1)j+i(1)i+(j1)det(111)=(1)2j+2i1=1.\det\p{T_{ij}} = \p{-1}^{j+i} \p{-1}^{i+\p{j-1}} \det \begin{pmatrix} 1 \\ & 1 \\ & & \ddots \\ & & & 1\end{pmatrix} = \p{-1}^{2j+2i-1} = -1.

    Here, we used the fact that detIn=1\det I_n = 1.

    Next, det(Tijt)=det(Tij)\det\p{T_{ij}^t} = \det\p{T_{ij}} since this is true for any matrix (or alternatively, you can say that TijT_{ij} is symmetric, so it's equal to its transpose).

    Lastly, to show that TijT_{ij} is its own inverse, we can just check it on a basis. If k{i,j}k \notin \set{i, j}, then

    Tij(Tijek)=Tijek=ek.T_{ij}\p{T_{ij}e_k} = T_{ij}e_k = e_k.

    And for k=ik = i,

    Tij(Tijei)=Tij(ej)=eiT_{ij}\p{T_{ij}e_i} = T_{ij}\p{e_j} = e_i

    and similarly for k=jk = j. Thus, Tij2=InT_{ij}^2 = I_n holds on a basis, and by linearity, it holds everywhere, so Tij1=TijT_{ij}^{-1} = T_{ij}.

  2. Like before, we can compute Di(m)D_i\p{m} on a basis. If kik \neq i, then Di(m)ek=ekD_i\p{m}e_k = e_k. Otherwise, Di(m)ei=meiD_i\p{m}e_i = me_i, so

    Di(m)=(1m1).D_i\p{m} = \begin{pmatrix} 1 \\ & \ddots \\ & & m \\ & & & \ddots \\ & & & & 1 \end{pmatrix}.

    Here, Di(m)D_i\p{m} is 00 except on the diagonal. At the (i,i)\p{i, i}-th entry, it has an mm, and it has a 11 everywhere else on the diagonal. Since the determinant of an upper-triangular matrix is just the product of the diagonal entries (you can prove this by induction and Laplace expansion),

    det(Di(m))=1××m××1=m.\det\p{D_i\p{m}} = 1 \times \cdots \times m \times \cdots \times 1 = m.

    Like before, det(Di(m)t)=det(Di(m))\det\p{D_i\p{m}^t} = \det\p{D_i\p{m}} since it's symmetric. Lastly, if m0m \neq 0, then we can just check that Di(m1)D_i\p{m^{-1}} is an inverse on a basis. If kik \neq i, then

    Di(m1)(Di(m)ek)=Di(m1)ek=ekD_i\p{m^{-1}}\p{D_i\p{m}e_k} = D_i\p{m^{-1}}e_k = e_k

    and if k=ik = i,

    Di(m1)(Di(m)ei)=Di(m1)(mek)=m(Di(m)1ei)=mm1ei=ei.\begin{aligned} D_i\p{m^{-1}}\p{D_i\p{m}e_i} &= D_i\p{m^{-1}}\p{me_k} \\ &= m \p{D_i\p{m}^{-1}e_i} \\ &= mm^{-1}e_i \\ &= e_i. \end{aligned}

    Thus, Di(m1)D_i\p{m^{-1}} is a left-inverse for Di(m)D_i\p{m}, and because Di(m)D_i\p{m} is a square matrix, it follows that it's also a right-inverse. In other words, Di(m)1=Di(m1)D_i\p{m}^{-1} = D_i\p{m^{-1}}.

  3. I will assume that iji \neq j. Otherwise, Lii(m)=Di(1+m)L_{ii}\p{m} = D_i\p{1 + m}, which is the previous case.

    When kjk \neq j, the jj-th row of eke_k is 00, so adding the jj-th row of eke_k to anything doesn't change it. Thus, Lij(m)ek=ekL_{ij}\p{m}e_k = e_k. On the other hand, if k=jk = j, then we add mm to the ii-th row of eke_k, which gives Lij(m)ej=ej+meiL_{ij}\p{m}e_j = e_j + me_i. Hence,

    Lij(m)=(11m11).L_{ij}\p{m} = \begin{pmatrix} 1 \\ & \ddots \\ & & 1 & \cdots & m \\ & & & \ddots & \vdots \\ & & & & 1 \\ & & & & & \ddots \\ & & & & & & 1 \end{pmatrix}.

    Like before, every entry is 00 except on the diagonal, which are all 11's, and except at the (i,j)\p{i, j}-th entry, which is mm. This is an upper-triangular matrix with all 11's on the diagonal, so its determinant is

    det(Lij(m))=1.\det\p{L_{ij}\p{m}} = 1.

    Note that Lij(m)tL_{ij}\p{m}^t is a lower-triangular matrix, but the determinant of this matrix has the same property: it's the product of its diagonal entries, so det(Lij(m)t)=1\det\p{L_{ij}\p{m}^t} = 1 also.

    Lastly, if kjk \neq j, then

    Lij(m)(Lij(m)ek)=Lij(m)ek=ek,L_{ij}\p{-m}\p{L_{ij}\p{m}e_k} = L_{ij}\p{-m}e_k = e_k,

    and if k=jk = j,

    Lij(m)(Lij(m)ej)=Lij(m)(ej+mei)=Lij(m)ej+mLij(m)ei=ejmei+mei=ej.\begin{aligned} L_{ij}\p{-m}\p{L_{ij}\p{m}e_j} &= L_{ij}\p{-m}\p{e_j + me_i} \\ &= L_{ij}\p{-m}e_j + mL_{ij}\p{-m}e_i \\ &= e_j - me_i + me_i \\ &= e_j. \end{aligned}

    Thus, Lij(m)L_{ij}\p{-m} is a left-inverse and Lij(m)L_{ij}\p{m} is a square matrix, it is invertible with Lij(m)1=Lij(m)L_{ij}\p{m}^{-1} = L_{ij}\p{-m}.

Problem 5

Let MMn×n(C)M \in M_{n \times n}\p{\C}, define the matrix M\conj{M} via (M)ij=Mij\p{\conj{M}}_{ij} = \conj{M_{ij}} for all i,j{1,,n}i, j \in \set{1, \ldots, n}.

  1. Prove that det(M)=det(M)\det\p{\conj{M}} = \conj{\det\p{M}}.
  2. Prove that Mt=(M)t\conj{M^t} = \p{\conj{M}}^t. Define M=MtM^* = \conj{M^t}.
  3. A matrix QMn×n(C)Q \in M_{n \times n}\p{\C} is called unitary if QQ=InQQ^* = I_n. Prove that if QQ is unitary, then detQ=1\abs{\det Q} = 1.
Solution.

The definition of the determinant we're using is

det(M)=j=1n(1)i+jMijdet(M^ij),\det\p{M} = \sum_{j=1}^n \p{-1}^{i+j} M_{ij} \det\p{\widehat{M}_{ij}},

where i{1,,n}i \in \set{1, \ldots, n} is any index, M^ij\widehat{M}_{ij} is the minor of MM we get from removing the ii-th row and jj-th column (i.e., the row and column that contains MijM_{ij}). Thus, if MM is an n×nn \times n matrix, then M^ij\widehat{M}_{ij} is an (n1)×(n1)\p{n-1} \times \p{n-1} matrix.

  1. We prove this by induction. The base case is n=1n = 1, where M=(m11)M = \p{m_{11}}. Then

    det(M)=det(m11)=m11=det(M),\det\p{\conj{M}} = \det\p{\conj{m_{11}}} = \conj{m_{11}} = \conj{\det\p{M}},

    so the base case holds. For the inductive step, assume that det(N)=det(N)\det\p{\conj{N}} = \conj{\det\p{N}} for any n×nn \times n matrix NN. We need to show it holds for any (n+1)×(n+1)\p{n+1} \times \p{n+1} matrix. Let MM be an (n+1)×(n+1)\p{n+1} \times \p{n+1} matrix. Then

    det(M)=j=1n(1)i+jMijdet(Mij^).\det\p{\conj{M}} = \sum_{j=1}^n \p{-1}^{i+j} \conj{M_{ij}} \det\p{\widehat{\conj{M_{ij}}}}.

    Note that Mij^\widehat{\conj{M_{ij}}} is an n×nn \times n matrix, so by the inductive hypothesis,

    det(Mij^)=det(Mij^).\det\p{\widehat{\conj{M_{ij}}}} = \conj{\det\p{\widehat{M_{ij}}}}.

    Also, recall that complex conjugation is additive and multiplicative: for z,wCz, w \in \C, we have z+w=z=w\conj{z + w} = \conj{z} = \conj{w} and zw=zw\conj{zw} = \conj{z} \conj{w}. Lastly, note that (1)i+j=(1)i+j\conj{\p{-1}^{i+j}} = \p{-1}^{i+j} since it's a real number. Putting everything together,

    det(M)=j=1n(1)i+jMijdet(M^ij)=j=1n(1)i+jMijdet(Mij^)=j=1n(1)i+jMijdet(Mij^)=det(M).\begin{aligned} \det\p{\conj{M}} &= \sum_{j=1}^n \p{-1}^{i+j} \conj{M_{ij}} \det\p{\conj{\widehat{M}_{ij}}} \\ &= \sum_{j=1}^n \conj{\p{-1}^{i+j}} \conj{M_{ij}} \conj{\det\p{\widehat{M_{ij}}}} \\ &= \conj{\sum_{j=1}^n \p{-1}^{i+j} M_{ij} \det\p{\widehat{M_{ij}}}} \\ &= \conj{\det\p{M}}. \end{aligned}
  2. Recall that (At)ij=Aji\p{A^t}_{ij} = A_{ji} for any matrix AA. Thus,

    (Mt)ij=(Mt)ij=Mji=(M)ji=((M)t)ij.\p{\conj{M^t}}_{ij} = \conj{\p{M^t}_{ij}} = \conj{M_{ji}} = \p{\conj{M}}_{ji} = \p{\p{\conj{M}}^t}_{ij}.
  3. Recall that if A,BA, B are square, then det(AB)=det(A)det(B)\det\p{AB} = \det\p{A} \det\p{B}. Thus, if we compute the determinant on both sides of QQ=InQQ^* = I_n, then

    det(Q)det(Q)=det(QQ)=det(In)=1.\det\p{Q} \det\p{Q^*} = \det\p{QQ^*} = \det\p{I_n} = 1.

    But by the first part,

    det(Q)=det(Qt)=det(Qt)=det(Q).\det\p{Q^*} = \det\p{\conj{Q^t}} = \conj{\det\p{Q^t}} = \conj{\det\p{Q}}.

    Lastly, recall that if zCz \in \C, then zz=z2z\conj{z} = \abs{z}^2, so

    1=det(Q)det(Q)=det(Q)det(Q)=det(Q)2,1 = \det\p{Q} \det\p{Q^*} = \det\p{Q} \conj{\det\p{Q}} = \abs{\det\p{Q}}^2,

    which implies that det(Q)=1\abs{\det\p{Q}} = 1.